2022
DOI: 10.1111/and.14395
|View full text |Cite
|
Sign up to set email alerts
|

Perineural invasion detected in prostate biopsy is a predictor of positive surgical margin of radical prostatectomy specimen: A meta‐analysis

Abstract: The role of perineural invasion detected by puncture biopsy of prostate cancer remains controversial. We performed a meta-analysis to assess the relationship between positive perineural invasion at prostate biopsy and positive surgical margins (PSM) after radical prostatectomy. We searched a number of relevant electronic databases including Web of Science, Medline, PubMed, Embase, and the Cochrane Library until 31 March 2021. STATA 15.1 software was used to analyse all data for this article.The quality of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Two systemic reviews concluded that biopsy PNI is associated with positive surgical margins at RP as well as biochemical recurrence after operation and radiotherapy. 26,27 In a large multicentre study, Celik et al showed that biopsy PNI was also significantly associated with a posterolateral margin status and nervesparing surgery, although surgical procedures were not standardised as in the current study. 28 It is not clear whether the risk of positive surgical margins is increasing when PNI is observed in more biopsies.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Two systemic reviews concluded that biopsy PNI is associated with positive surgical margins at RP as well as biochemical recurrence after operation and radiotherapy. 26,27 In a large multicentre study, Celik et al showed that biopsy PNI was also significantly associated with a posterolateral margin status and nervesparing surgery, although surgical procedures were not standardised as in the current study. 28 It is not clear whether the risk of positive surgical margins is increasing when PNI is observed in more biopsies.…”
Section: Discussionmentioning
confidence: 71%
“…Biopsy PNI has been investigated extensively as a prognostic marker with variable outcomes. Two systemic reviews concluded that biopsy PNI is associated with positive surgical margins at RP as well as biochemical recurrence after operation and radiotherapy 26,27 . In a large multicentre study, Celik et al .…”
Section: Discussionmentioning
confidence: 99%
“…Some preoperative clinicopathological factors, such as clinical T stage, Gleason score, percentage of positive biopsy cores, and perineural invasion detected in prostate biopsy, have been reported to correlate with the risk of PSM [ 3 , 9 11 ]. In addition, pelvic anatomy is associated with PSM [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%